2021
DOI: 10.1210/clinem/dgab417
|View full text |Cite
|
Sign up to set email alerts
|

Intact Fasting Insulin Identifies Nonalcoholic Fatty Liver Disease in Patients Without Diabetes

Abstract: Context Patients with nonalcoholic fatty liver disease (NAFLD) are characterized by insulin resistance and hyperinsulinism. However, insulin resistance measurements have not been shown to be good diagnostic tools to predict NAFLD in prior studies. Objective We aimed to assess a newly validated method to measure intact molecules of insulin by mass spectrometry to predict NAFLD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Recently, the American Gastroenterological Association (AGA), in collaboration with members of other societies, published a NAFLD/NASH Clinical Care Pathway [8] . In this work, the authors identified three groups of patients at greatest risk of NAFLD/NASH-related fibrosis: 1) patients with T2D, 2) patients with two or more metabolic risk factors, and 3) patients with incidental findings of hepatic steatosis or elevated aminotransferases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, the American Gastroenterological Association (AGA), in collaboration with members of other societies, published a NAFLD/NASH Clinical Care Pathway [8] . In this work, the authors identified three groups of patients at greatest risk of NAFLD/NASH-related fibrosis: 1) patients with T2D, 2) patients with two or more metabolic risk factors, and 3) patients with incidental findings of hepatic steatosis or elevated aminotransferases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems intuitive including other 'at risk' groups in the guidelines, such as patients with diabetes and those with metabolic risk factors. However, these and other guidelines [4,8,18] recommend initiating the screening for advanced liver fibrosis with non-invasive tests, which rely heavily on plasma aminotransferase elevations, so patients with normal plasma aminotransferases may still go undiagnosed with these tools. Therefore, adding more 'at risk' groups may not provide an advantage over just selecting patients based on elevated plasma aminotransferases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations